Assessing the efficiency of bamboo biochar in microcystin-LR removal from water (INNOTEC, 2024)
Developing sustainable and cost-effective adsorbents for removing microcystin-LR (MCLR) is crucial. Bambusa Tuldoides was pyrolyzed at various temperatures (400, 500, and 600 °C) and residence times (0.5 and 2 h) to produce a series of biochars. The observed MCLR adsorption capacity (219 μg g-1 for 600B0.5 sample) under pH conditions similar to those in a water treatment plant (pH = 7.6) is mainly attributed to hydrophobic interactions, π-π stacking, and the basic nature of the biochars (pHpzc > 8). A comprehensive analysis, including FTIR, elemental and proximate analysis, TG, SEM, N2 adsorption, Hg porosimetry and Raman spectroscopy support this finding. Additionally, to compare 600B0.5 with commercially available activated carbon, a dynamic study was conducted using actual contaminated water. 600B0.5 sample exhibits a removal efficiency of 99.5 %, resulting in a final concentration of 0.28 μg L-1, well below the World Health Organization guideline of 1 μg L-1.
Keywords: biomass; pyrolysis; carbon; adsorption; cyanotoxin